使用高頻超音波定量評估不同鯨豚物種皮膚 - 葉信賢; Yeh, Shin-Shian (2019)
海洋哺乳類中，鯨豚類一直是人們感興趣的對象。從17、18世紀的捕鯨以取得鯨脂、鯨肉，到現代人們保育意識抬頭，以保護鯨豚和賞鯨提供了不同的經濟價值，鯨豚已成為人類世界的一部分。在過往中有許多關於鯨豚皮膚組織的研究，發現到皮膚組織可以去描述它們生前的生活環境、營養狀態或是體內器官的健康程度。在皮膚分層中已經被以前的研究歸類成表皮層和包含真皮層和皮下組織的鯨脂，在不同的個體中會有不小的差異(如表皮組成或鯨脂中脂肪組織分布)，這些均是由電子顯微影像或是切片染色中取得。鑒於先前研究使用超音波對皮膚組織的分析，超音波具有非侵入、快速和量測花費便宜等優點，但在掃描時會受到聚焦區域的影響，本研究將使用掠表面掃描克服超出聚焦區的問題，並使用25MHz之高頻超音波換能器對小虎鯨、侏儒抹香鯨和弗式海豚不同部位(位置3、4、5、6)進行量測，實驗中會以距表面固定深度為量測距離，並使用聲速、衰減、積體逆散射、Nakagami參數來分析不同深度之組織特性。結果顯示鋼塊反射在進行水平掃描時，在20.6 mm時訊雜比(SNR)為24.63但在深度到達22.8 mm超出聚焦區後SNR變成20.25，而使用掠表面掃描後，在20.6 mm時SNR為24.51而在達到22.8 mm後為24.62，在因角度造成的假影中，水平掃描在22.8 mm有明顯比20.6 mm更強的假影訊號產生。在小虎鯨的分析上，在背鰭附近皮膚和下半部皮膚聲速成下降趨勢，而衰減則約在深度1.5 mm位置後均大於10 dB/mm，Nakagami參數顯示隨著深度增加，參數有上升的趨勢。侏儒抹香鯨的聲速在深度為1 mm時位置3高於位置4而其餘皆低於，衰減上隨著深度增加，衰減呈現上升趨勢但相比於小虎鯨和弗式海豚較沒有跳躍性間隔，Nakagami參數在除了2 mm時呈現下降趨勢，其餘皆是上升趨勢。弗式海豚聲速上呈緩慢下降趨勢，而衰減在1.5 mm後大於15 dB/mm，Nakagami參數和侏儒抹香鯨一樣在2 mm後下降，從0.5 mm至1.5mm皆是上升。在積體逆散射參數中，三種鯨豚類皆呈現下降趨勢，但是並不能確定是由衰減或是組織組成所造成的影響，而使用頻率上的衰減補償並無法達到好的衰減補償效果，可能是因為組織不均質和雜訊所造成的結果。在這個實驗中，真皮的厚度、脂肪組織的濃度、取樣位置是可以由超音波參數去判別出來的，證明了使用超音波去特性化不同鯨豚皮膚組織和結構是可行的。 Marine mammal cetacean have been interest by human for centuries In the 17th 18th century whaling is an important economic activity and whaling watching protection provide other value until late 20th century In the past research of cetacean skin skin is affected by environment nutritional status and internal tissue condition The layers of cetacean skin are classified as epidermis and blubber which contains dermis and subcutis and different individuals have significance variance (e g composition of epidermis and concentration of adipose tissue) Most of the results are analyzed by electron microscopy and slice staining In view of past researches analying on skin by ultrasound ultrasound is good at non-invasive diagnosis fast and cost-effective scanning But focal region is a big problem on ultrasound imaging because of resolution and noise effect Therefore in this study surface skimming is used to overcome beyond focal region A high frequency ultrasound which is equipped 25 MHz transducer is used to measure different body parts (position 3 4 5 6) of Pygmy killer whale Dwarf sperm whale and Fraser’s dolphin The experiment is based on depth from surface and use sound speed attenuation Integrated backscatter (IB) Nakagami parameter for characterization Results show that the signal to noise ratio (SNR) of rf signal from steel using horizontally scanning are 24 63 at 20 6 mm and 20 25 at 22 8 mm The SNR of rf signal from steel using surface skimming are 24 51 at 20 6 mm and 24 62 at 22 8 mm The artifact effect using surface skimming is not more obvious than horizontally scanning The sound speed of Pygmy killer whale decrease as depth increase and attenuation at depth 1 5 mm and 2 mm is higher than 10 dB/mm compared with 0 5 mm and 1 mm Nakagami parameters shows increasing trend as depth increase Sound speed of Dwarf sperm whale position 3 at depth 1 mm is higher than position 4 however depth 0 5 mm 1 5mm 2 mm at position 3 are lower than position 4 Attenuation coefficient increase as depth increase but progressive growth compared with Pygmy killer whale and Fraser’s dolphin which is clearly separated at depth 9 mm Nakagami parameter increase from 0 5 mm to 1 5 mm and decrease from 1 5 mm to 2 mm Speed sound of Fraser’s dolphin decrease slowly as depth increase Attenuation is higher than 15 dB/mm from 1 5 mm and 0 5 mm 1 mm are lower than 10 dB/mm Nakagami parameter have the same trend as Dwarf sperm whale decreasing from 1 5 mm to 2 mm and increasing from 0 5 mm to 1 5 mm The IB of three species have the decreasing trend which is undetermined that be caused by attenuation or composition of tissue And compensation of frequency-dependent power spectra is not ideal because of inhomogeneity of tissue and noise effect In this study thickness of epidermis concentration of adipose tissue and sampling position can be determined by ultrasounonic parameters The study indicate that it is feasible to characterize composition and structure of cetacean skin by ultrasound 資訊工程學系 電機資訊學院 博碩士論文